Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s12603-013-0390-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability during gait initiation while dual tasking is increased in individuals with mild cognitive impairment

Abstract: Step length and step width variability is increased in people with MCI during GI, particularly in a condition involving a secondary cognitive task. These findings suggest that individuals with MCI have reduced balance control when undertaking a challenging walking task such as gait initiation, and this is exacerbated with an added cognitive task. Future studies should prospectively investigate the relationship between GI variability and fall risk in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…Results for DTC studies using counting or spelling backwards found that gait speed (and other characteristics) declined and variability (e.g., step length, step width, cadence) increased (Boripuntakul et al, 2014;Coelho et al, 2012). Significant correlations between fluency (naming of animals) and executive function (Clock Drawing scores), and DTC gait characteristics (e.g., cadence, stride length, velocity) were found in a sample (N = 50) of participants with early-stage dementia (Bruce-Keller et al, 2012).…”
Section: Changes In Gait and Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Results for DTC studies using counting or spelling backwards found that gait speed (and other characteristics) declined and variability (e.g., step length, step width, cadence) increased (Boripuntakul et al, 2014;Coelho et al, 2012). Significant correlations between fluency (naming of animals) and executive function (Clock Drawing scores), and DTC gait characteristics (e.g., cadence, stride length, velocity) were found in a sample (N = 50) of participants with early-stage dementia (Bruce-Keller et al, 2012).…”
Section: Changes In Gait and Balancementioning
confidence: 99%
“…Six studies examined gait characteristics under dual task conditions (DTCs) among individuals with MCI (Boripuntakul et al, 2014;Cedervall et al, 2014;Coelho et al, 2012;Montero-Odasso et al, 2012;Muir, Speechley, et al, 2012;. DTCs involve use of attentional resources or distraction activities while walking, which can vary in complexity.…”
Section: Changes In Gait and Balancementioning
confidence: 99%
See 1 more Smart Citation
“…The gait disorders reported in MCI patients include (i) decreases in gait speed (Pettersson et al 2007;Maquet et al 2010;MonteroOdasso et al 2009a;Montero-Odasso et al 2012;Muir et al 2012;Doi et al 2014;Tseng et al 2014;Tarnanas et al 2015) and stride length (Montero-Odasso et al 2009b;Maquet et al 2010) and (ii) increases in stride time , swing time (Boripuntakul et al 2014), stride length variability (Boripuntakul et al 2014), double support time variability (MonteroOdasso et al 2009b), and stride time variability (Camicioli et al 2006;Allali et al 2007;MonteroOdasso et al 2009b;Muir et al 2012;Ijmker and Lamoth 2012;Montero-Odasso et al 2014). From a neuropathological point of view, dual-task-related gait changes were interpreted as resulting from impairments in working memory and executive attention control (Maquet et al 2010), both altering the ability of patients to execute more than one task at a time.…”
Section: Prodromal Phase Of Alzheimer's Diseasementioning
confidence: 99%
“…Slower and more variable walking patterns are associated with reduced quality of life, greater disability, falls and increased mortality . Several studies have identified a range of sensorimotor, psychological, cognitive and health impairments that are associated with reduced gait performance in the clinic . For example, strength, postural sway, reaction time, contrast sensitivity and pain are all predictors of clinical gait speed in older people …”
Section: Introductionmentioning
confidence: 99%